2001
DOI: 10.1111/1467-9515.00235
|View full text |Cite
|
Sign up to set email alerts
|

Family Support for Old People in Rural China

Abstract: In China the family is still the major welfare provider for old people in rural areas. Although the implementation of this role has varied significantly, in different historical periods, owing to social and economic changes in the rural environment, the core functions of the family have remained the same, that is, the provision of welfare for dependants, particularly for the aged. In the more traditional China, providing care for the aged was indeed assumed to be a paramount function of the family. Whereas, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 0 publications
1
69
0
Order By: Relevance
“…Various researchers (e.g. Cooney & Di, 1999;Fong, 2004;Miller, 2004;Xu, 2001;Yang, 1996) have found daughters to be heavily involved in their parents' lives, most obviously when they do not have brothers. Even when they do have brothers, however, daughters visit often, offering instrumental, emotional and financial support.…”
Section: Economic Reform and Intergenerational Relationships 391mentioning
confidence: 99%
“…Various researchers (e.g. Cooney & Di, 1999;Fong, 2004;Miller, 2004;Xu, 2001;Yang, 1996) have found daughters to be heavily involved in their parents' lives, most obviously when they do not have brothers. Even when they do have brothers, however, daughters visit often, offering instrumental, emotional and financial support.…”
Section: Economic Reform and Intergenerational Relationships 391mentioning
confidence: 99%
“…Furthermore, some studies (e.g., Davis-Friedman, 1991;Whyte, 1995;Xiang, 2007;Xu, 2001;Yan, 1997) indicated that the elderly in China have lost control over resources as the balance of power has shifted away from them and that there has been a worsening of economic standing of the elderly both inside and outside the extended household. For example, the economic and social system changes in China since the foundation of People's Republic of China have removed the economic foundation (private ownership of property such as land) supporting the status of the aged in the family (Xu, 2001). In addition, it was argued that the changes due to modernization and urbanization could be stressful and erode older people's life satisfaction (Cheung & Leung, 2004;Nee, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Non-family members do not report providing care for friends or neighbours. This could be an artifact of the sampling procedure, but it may also be that to go outside the family for help would imply that one's own family is not filial in handling all of the care (Xu 2001, Asahara et al 2002, Knight et al 2002.…”
Section: Differencesmentioning
confidence: 99%